INTERSECTION OF EDUCATION AND ARTIFICIAL INTELLIGENCE - Mannappan, Selvakumaran (Global journal of Business and Integral Security, 2024)
Artificial intelligence is certainly changing the world and like many fields in the world, education field is also impacted positively by this change. But there are aspects which needs to be carefully monitored and controlled so that the world can understand this change well and transition to a new world where the learning can fundamentally be different from what we all have gone through in our life and can be a lot more productive and constructive.